PEMBERDAYAAN MASYARAKAT UNTUK MENANAMKAN NILAI TOLERANSI UMAT BERAGAMA PADA SISWA DI SDN 1 MOJOPURO - Raudhatul Ikrimah; Nur Najmi Laila Azami; Erhan Habli Muttaqin; Muhtar Mochamad Solihin (PPM Universitas Telkom, 2026)
The Religious Harmony Class (KUB) program is a form of religious outreach activity aimed at internalizing tolerance values from an early age among students of SDN 01 Mojopuro, Jatiroto District, Wonogiri Regency. This activity was motivated by the importance of instilling tolerance in a multicultural society to enable young generations to appreciate diversity and maintain interfaith harmony. The implementation consisted of three stages—planning, implementation, and evaluation—conducted over three weeks. The program was tailored to students’ developmental levels through the use of interactive media such as flash cards, animated films, educational games, and role play. The results of pre- and post-tests indicated a significant improvement in students’ understanding and attitudes toward tolerance across all grade levels. Students were able to recognize Indonesia’s six official religions and their places of worship, as well as demonstrate respectful and cooperative behavior in social interactions. Experience-based and visual learning proved effective in fostering cognitive and affective aspects of tolerance. This activity contributes to the development of a character education model relevant to local contexts and elementary school students’ needs.